(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
The view of Hamas as an insurgent movement seeking the destruction of Israel and the construction of an Islamic State on historical Palestinian territory is based on its own doctrine, known as the “muqawama” or resistance doctrine. The “muqawama doctrine” has its own distinctive elements and is independent of classical insurgency frameworks; hence, these new elements constitute a valuable analytical tool for the study of emerging insurgent and Islamist phenomena.